A TolC-Like Protein of Actinobacillus pleuropneumoniae Is Involved in Antibiotic Resistance and Biofilm Formation - Li, Ying; Cao, Sanjie; Zhang, Luhua; Lau, Gee W.; Wen, Yiping; Wu, Rui; Zhao, Qin; Huang, Xiaobo; Yan, Qigui; Huang, Yong; Wen, Xintian (Frontiers in Microbiology, 2016)
Actinobacillus pleuropneumoniae is the etiologic agent of porcine contagious pleuropneumonia, a significant disease that causes serious economic losses to the swine industry worldwide. Persistent infections caused by bacterial biofilms are recalcitrant to treat because of the particular drug resistance of biofilm-dwelling cells. TolC, a key component of multidrug efflux pumps, are responsible for multidrug resistance in many Gram-negative bacteria. In this study, we identified two TolC-like proteins, TolC1 and TolC2, in A. pleuropneumoniae. Deletion of tolC1, but not tolC2, caused a significant reduction in biofilm formation, as well as increased drug sensitivity of both planktonic and biofilm cells. The genetic-complementation of the tolC1 mutation restored the competent biofilm and drug resistance. Besides, biofilm formation was inhibited and drug sensitivity was increased by the addition of phenylalanine-arginine beta-naphthylamide (PAβN), a well-known efflux pump inhibitor (EPI), suggesting a role for EPI in antibacterial strategies towards drug tolerance of A. pleuropneumoniae. Taken together, TolC1 is required for biofilm formation and is a part of the multidrug resistance machinery of both planktonic and biofilm cells, which could supplement therapeutic strategies for resistant bacteria and biofilm-related infections of A. pleuropneumoniae clinical isolate SC1516.